Kedudukan Hak Atas Tanah yang Telah Dialihkan Sebagai Bagian Boedel Pailit (Studi Kasus PT. Salam Teguh Perkasa) - Fairuz Syahid Agata; Riky Rustam (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
This research is motivated by the existence of legal problems regarding the validity of the transfer of land rights where the land object is then used as a bankruptcy estate. The purpose of this research is to find out how the validity of the transfer of land rights that have been transferred by the parties and the validity of the land object which is then used as a bankruptcy estate. This research typology uses normative legal research. Normative legal research is research that refers to legal norms contained in laws and regulations and court decisions. The approach method used is the statutory approach and conceptual approach. The results of this study are related to the transfer of land objects carried out by Syaiful to Agung Nugroho is valid while that carried out by Agung Nugroho to Hermawan is invalid, this is based on the difference in the transfer time, namely the PPJB paid off and the PPJB has not been paid off. Then related to the validity of the land object used as the bankruptcy estate of PT STP is invalid because the object has not become the property of PT STP when it is used as a bankruptcy estate. The legal advice that can be given is that Hermawan as an aggrieved buyer can file a legal action in the form of a tort claim against Agung Nugroho to the Bantul District Court. The second legal advice is that Agung Nugroho can again file a lawsuit to the Semarang Commercial Court so that the land object can be removed from the bankruptcy estate of PT. STP.